APLIKASI PENDATAAN LOKASI BANK, ATM, DAN SPBU DI KOTA PADANG BERBASIS ANDROID - Elizamiharti, Elizamiharti; Amuharnis, Amuharnis; Yeni, Indri; Rahmadani, Ardarini (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2021)
Padang city is the capital of West Sumatera province which is developing in various fields, one of them is banking field. The amount of ATM distribution makes people difficult to memorize and know where the ATM location. Likewise with gas stations, many of the community, immigrants and tourists who do not know the location of the city Padang SPBU in the city of Padang. Through the design and development of location-based mobile data collection applications android this can facilitate the community, immigrants and tourists in finding information on the location of banks, ATMs and gas stations in the city of Padang. The method used is the method of data collection and survey analysis, while the design method using SDLC method with waterfall model. This application uses haversine formula as a calculation method that is considered suitable for nearest location search because in the calculation process to take into account the curvature of the earth so it can produce more accurate results. With this application android phone users can find out the location of banks, ATMs and gas stations that are closest to where they are located.